PENGEMBANGAN MODEL PEMBELAJARAN KEAKSARAAN FUNGSIONAL BERBASIS POTENSI PERTANIAN BAGI PEMBERDAYAAN KOMUNITAS ADAT TERPENCIL - Saing Mahu (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2011)
The problems of illiteracy and poverty have not been optimally overcome through the development of functional literacy program based on local potential. This research aims to develop literacy-based learning model to empower the local potential of the Remote Indigenous Communities. This study employed research and development approach and the data were collected using questionnaires, interviews, and documentation study. The respondents consisted of the program, traditional leaders / community, tutors, and program participants in five villages PKBM organizers, District Waiapo . The research producedliteracy learning model which has significant positive effect on the empowerment of remote indigenous communities in the functional literacy program.